'This was like some Little House on the Prairie shit': The intensive care(work) of making PPE during COVID-19. (15th March 2023) - Stalp, Marybeth; Leap, Braden; Kelly, Kimberly
Abstract: In March 2020 during the first wave of COVID-19 in the United States, the national supply and distribution of personal protective equipment (PPE) was dangerously underwhelming. Skilled volunteer quilters, sewists and 3D printer enthusiasts emerged in a groundswell of life-saving gendered disaster response, creating face masks, ear savers, and face shields. Making PPE was both tiring and comforting, a distraction from, and solution to, the pandemic, revealing the tense overlap between volunteering and project-based leisure opportunities. Qualitative data collected from July 2020 to January 2021 demonstrate PPE makers engaging in carework for the self—turning to a chosen leisure activity to relieve anxiety and provide a needed momentary distraction from the pandemic, and carework for others—constructing and distributing PPE for those in need.